Reimagining Online and Blended Provision of English for Academic Purposes - Jean Antunes; Mariam Farooq (Teacher Education through Flexible Learning in Africa, 2022)
The online and blended delivery of courses through the use of technologies has attracted attention and research.The teaching and learning of English for Academic Purposes (EAP) in multilingual contexts such as in Africa has also been given prominence in research, as well as the benefits of technology in EAP programmes. The pressing need for technology - supported educational practices has been evidenced by the COVID-19 pandemic that affected most educational systems around the world. Although there is an increasing body of research on the integration of technology in education emerging from developing contexts, most proposed models still come from high-income countries.Therefore, there is a need for more critical and contextually relevant approaches to the integration of technology in education. Based on the authors’ narratives of their lived experiences as teachers of EAP in a university in East Africa, this article aims to describe and reflect on the practices related to design and delivery of online and blended courses to university students, including in a teacher education programme. It is hoped that this work will contribute to discussions on how to make online and blended teaching practices of EAP more contextually relevant and how exogenous resources can be adapted to the realities of students in multilingual developing contexts.